VasH Contributes to Virulence of Aeromonas hydrophila and Is Necessary to the T6SS-mediated Bactericidal Effect - Li, Jihong; Wu, Zhihao; Wu, Changsong; Chen, Dan-Dan; Zhou, Yang; Zhang, Yong-An (Frontiers in Veterinary Science, 2021)
Aeromonas hydrophila is a Gram-negative bacterium that is commonly distributed in aquatic surroundings and has been considered as a pathogen of fish, amphibians, reptiles, and mammals. In this study, a virulent strain A. hydrophila GD18, isolated from grass carp (Ctenopharyngodon idella), was characterized to belong to a new sequence type ST656. Whole-genome sequencing and phylogenetic analysis showed that GD18 was closer to environmental isolates, however distantly away from the epidemic ST251 clonal group. The type VI secretion system (T6SS) was known to target both eukaryotic and prokaryotic cells by delivering various effector proteins in diverse niches by Gram-negative bacteria. Genome-wide searching and hemolysin co-regulated protein (Hcp) expression test showed that GD18 possessed a functional T6SS and is conditionally regulated. Further analysis revealed that VasH, a σ54-transcriptional activator, was strictly required for the functionality of T6SS in A. hydrophila GD18. Mutation of vasH gene by homologous recombination significantly abolished the bactericidal property. Then the virulence contribution of VasH was characterized in both in vitro and in vivo models. The results supported that VasH not only contributed to the bacterial cytotoxicity and resistance against host immune cleaning, but also was required for virulence and systemic dissemination of A. hydrophila GD18. Taken together, these findings provide a perspective for understanding the VasH-mediated regulation mechanism and T6SS-mediated virulence and bactericidal effect of A. hydrophila.